Charles H. Hamilton, ed., The General Ordinances of the City of Milwaukee to January 1, 1896: With Amendments Thereto and an Appendix (Milwaukee, WI: E. Keough, 1896), pp.692-93, Sec. 25 - (:unkn) unknown (My University, 1896)
It shall be unlawful for any person except policemen, regular or special, or any officer authorized to serve process, to carry or wear concealed about his person, any pistol or colt, slung-shot, cross-knuckles, knuckles of lead, brass or other metal, or bowie -knife, dirk knife, or dirk or dagger, or any other dangerous or deadly weapon, within the limits of the city of Milwaukee
Keywords: CARRY - CONCEALED